IMPACT OF GROUP B STREPTOCOCCUS ON THE MOTION OF PREGNANCY, LABOR AND POSTPARTUM PERIOD OF GBS-POSITIVE PREGNANT AFTER IVF - Perebenduk, T.V. (World of Medicine and Biology, 2014)
The motion of pregnancy and labor at GBS-positive pregnant women after IVF against application of various schemes of prevention and treatment of intra-uterine GBS-infection of a fetus is studied. It is established that the exacerbation of urogenital pathology during pregnancy, undoubtedly associates with GBS-colonization of the pregnant woman. When using the offered scheme of treatment-prophylactic actions of intra-uterine infection of a fetus reliable reduction of number of pregnant women with complications is observed during pregnancy and labor.
Keywords: IVF; intra-uterine infection; group B streptococcus; pregnancy; labor